Low-Dose Radiotherapy for Late-Stage COVID-19 Pneumonia? - Michael I. Koukourakis (SAGE Publishing, 2020)
Low dose radiotherapy has been used in the pre-antibiotic era for the treatment of all kind of pneumonia, with relative success. The unimaginable daily death toll of thousands of victims dying from COVID-19 pneumonia and the marginal therapeutic value of agents tested, brings forward the re-evaluation of the position of radiotherapy in the treatment of late stage lethal COVID-induced respiratory failure. A sound biological rationale supports this idea. Immunopathology studies show that excessive inflammation and infiltration of the lung parenchyma by immune cells is the cause of death. Mice lacking IFNαβ receptors remain unaffected by the virus. Radiotherapy at doses of 50-200cG may exert an intense anti-inflammatory effect and reduce the burden of inflammatory cells infiltrating the lungs. Whether radiotherapy, in conjunction with remdesivir and/or macrolides can reduce the dramatic death rates related to COVID-19 is an open challenge, under the absence of an alternative solution.